Culture of interethnic relations as a condition of formation of youth tolerant consciousness - Кукубаева, А. Х.; Бердибаева, Света Кыдырбековна; Мун, Мария Владимировна (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2017)
The article deals with the issues of interethnic communication of youth in multiethnic country. This sphere reflects certain, sometimes unpredictable, contradictory actions of people. Lack of knowledge about other peoples and national stereotypes are cause of psychological dissatisfaction among the people, which later transfer to ethnic violence. The task is to explore psychological diagnosis on students’ relationships and consider their need to communicate with their peers, their aggressiveness towards each other, as well as the cultural and value orientations of different nationalities. The authors reveal the peculiarities of cross-cultural interactions among adolescents. It is noticeable that the low level of culture interactions hinders processes in a multicultural society and does not contribute to the formation of a peaceful model of youth interethnic communication. At the same time, traditions of international relations are of great importance. The authors focus on the need to develop a culture of international relations at school. And for that, the authors consider the great importance of ethnic tolerance as the acceptation of internal individual attitude to cultural values of other ethnic groups, and readiness to inter-ethnic contacts. The authors have determined the main methodological approaches to the study of personality and formation of tolerant consciousness of teenagers; defined dynamics and cross-cultural differences in young people’s relationships, which have practical orientation. Particular attention is drawn to ethnic tolerance, which is considered the dominant of interethnic relations’ culture. There justified the necessity of direct educational strategy to form positive tolerant attitudes in the society. The authors propose the most optimal method of forming tolerance – it is education, which contributes to children’s tolerance while maintaining their own identity. Personality is actively involved into adulthood and forms its identity precisely in society. Key words: interethnic communication, tolerance, personality theories, activity approach, personality orientation, ethnic groups, interethnic tolerance.